Plate Tectonics : Tenerife's new cultural complex, TEA, brings a bold, dramatic topography to the centre of Santa Cruz, resonant of the island's volcanic provenance
Biblioteca, galería y museo en Tenerife, arquitectos Herzog & de Meuron.